Characterization of Salmonella isolated from organically reared poultry located in the same longitude with three distinct seasonal characteristics - Incili, Gokhan Kursad; Koluman, Ahmet; Dikici, Abdullah; Kahraman, Tolga; Unlu, Abdullah Teoman (Wiley, 2019)
This study is designed to determine Salmonella prevalence in organic poultry farms and slaughterhouse in three different regions with distinct seasonal characteristics. Salmonella strains were isolated from organic reared poultry farm environment (water, feed, and feces) and poultry meat samples (neck skin and breast meat). Antibiotic resistance and 16S rRNA profiles were demonstrated with alignment scores. Salmonella spp. prevalences according to regions were, 51 of 200 (25.50%) samples taken from Region A, 77 of 200 (38.50%) samples taken from Region B, 105 of 200 (52.50%) samples taken from Region C. Serotyping of the strains revealed that S. Typhimurium and S. Enteritidis are the most dormant strains among all strains. Antibiotic susceptibility of the strains revealed that major resistance against ampicillin. This study is held for an awareness rising about the possible impact of seasonality related with food borne pathogens prevalence.
Keywords: Time-Series Analysis; Antimicrobial Resistance; Antibiotic-Resistance; Chicken Meat; Microbiological Quality; Ambient-Temperature; Climate-Change; Prevalence; Serovars; Spp.